Altered plasma membrane abundance of the sulfatide-binding protein NF155 links glycosphingolipid imbalances to demyelination - McKie, Shannon J; Nicholson, Alex S; Smith, Emily; Fawke, Stuart; Caroe, Eve R; Williamson, James C; Butt, Benjamin G; Kolářová, Denisa; Peterka, Ondřej; Holčapek, Michal; Lehner, Paul J; Graham, Stephen C; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2023)
Myelin is a multilayered membrane that tightly wraps neuronal axons, enabling efficient, high-speed signal propagation. The axon and myelin sheath form tight contacts, mediated by specific plasma membrane proteins and lipids, and disruption of these contacts causes devastating demyelinating diseases. Using two cell-based models of demyelinating sphingolipidoses, we demonstrate that altered lipid metabolism changes the abundance of specific plasma membrane proteins. These altered membrane proteins have known roles in cell adhesion and signaling, with several implicated in neurological diseases. The cell surface abundance of the adhesion molecule neurofascin (NFASC), a protein critical for the maintenance of myelin-axon contacts, changes following disruption to sphingolipid metabolism. This provides a direct molecular link between altered lipid abundance and myelin stability. We show that the NFASC isoform NF155, but not NF186, interacts directly and specifically with the sphingolipid sulfatide via multiple binding sites and that this interaction requires the full-length extracellular domain of NF155. We demonstrate that NF155 adopts an S-shaped conformation and preferentially binds sulfatide-containing membranes in cis, with important implications for protein arrangement in the tight axon-myelin space. Our work links glycosphingolipid imbalances to disturbance of membrane protein abundance and demonstrates how this may be driven by direct protein-lipid interactions, providing a mechanistic framework to understand the pathogenesis of galactosphingolipidoses.
Keywords: glykosfingolipidy; Sulfoglycosphingolipids; Glycosphingolipids; transportní proteiny; Nerve Growth Factors; demyelinizační nemoci; Carrier Proteins; lidé; myelinová pochva; neurotrofní faktory; Demyelinating Diseases; molekuly buněčné adheze; Cell Adhesion Molecules; sulfoglykosfingolipidy; Myelin Sheath; Humans